2023
DOI: 10.17582/journal.aavs/2023/11.5.820.831
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Two Distinct Genotypes of Highly Pathogenic Avian Influenza A/H5n8 Viruses in Backyard Waterfowls in Upper Egypt During 2018

Abstract: H PAI viruses is a source of major concern for poultry and human health. The hemagglutinin (HA) genes of subtype H5 evolved through reassortment with various neuraminidase subtypes (1-9) to comprise AI H5NX viruses. The co-circulation of group A viruses with low patho-genic avian influenza (LPAI) viruses resulted in emergence of novel reassortants; H5N1 and H5N8 (El-Shesheny et al., 2017). H5N8 viruses has been emerged in Asia since 2010 where the first outbreaks in breeding ducks occurred in China then South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
(46 reference statements)
3
2
0
Order By: Relevance
“…No positive H5N1 viruses were reported in the surveyed flocks during our active surveillance which proves a little further circulation of HPAI H5N1 in the poultry population in Egypt during 2023 as in accordance with previous reports of [12,25]. While the prevalence rate of HPAIV H5N8 in our study was 28.3% from vaccinated broilers and layers chickens which is nearby the previously detected results of [13,21,23,26,27]. Whereas Salaheldin et al [28] detected the H5N8 viral infection by QrRT-PCR with higher prevalence rate of 45.1% in vaccinated chicken flocks.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…No positive H5N1 viruses were reported in the surveyed flocks during our active surveillance which proves a little further circulation of HPAI H5N1 in the poultry population in Egypt during 2023 as in accordance with previous reports of [12,25]. While the prevalence rate of HPAIV H5N8 in our study was 28.3% from vaccinated broilers and layers chickens which is nearby the previously detected results of [13,21,23,26,27]. Whereas Salaheldin et al [28] detected the H5N8 viral infection by QrRT-PCR with higher prevalence rate of 45.1% in vaccinated chicken flocks.…”
Section: Discussionsupporting
confidence: 92%
“…The HA glycoprotein is the primary determinant of Influenza A viruses virulence with receptor binding properties [30]. The HA cleavage site of the most previously isolated H5N8 strains encodes the motif PLREKRRKR/GLF which is characteristic for pathogenicity of those isolates, our results concluded that and were similar to other recent investigations by many studies [6,13,21,23,31] who concluded that their selected H5N8 isolates have the same motif in HA cleavage site. Furthermore, the genetic analysis of AA identity percent showed that our study isolates have identity percent among each others varied from 99.0 to 99.7% as in previously reported by Setta et al [23] and similar to our results who detected a close proximity to their H5N8 isolates to each others, while found them spaced out in AA identity percent of their isolates with H5 vaccinal strains.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations